Improving the Optical Properties of Self-Catalyzed GaN Microrods toward Whispering Gallery Mode Lasing - Tessarek, Christian; Roeder, Robert; Michalsky, Tom; Geburt, Sebastian; Franke, Helena; Schmidt-Grund, Ruediger; Heilmann, Martin; Hoffmann, Bjoern; Ronning, Carsten; Grundmann, Marius; Christiansen, Silke (ACS Photonics, 2014)
GaN microrods were grown self-catalyzed by a fast and simple metal–organic vapor phase epitaxy method without any processing before or after deposition. The prismatic microrods with a regular hexagonal cross-section, sharp edges, straight, and smooth sidewall facets act as a microresonator, as seen by the appearance of whispering gallery modes in the yellow defect band range. To improve their optical properties, a reduced Ga precursor flow is required during growth. However, their hexagonal microrod morphology is not maintained under these growth conditions. The approach to start growth with a high Ga precursor flow and applying a ramp to a reduced precursor flow yield in significant enhancement of the near band edge emission in the upper part of the microrods. Whispering gallery modes in superposition with the near band edge emission can now be detected by cathodoluminescence measurements. These improvements lead to stimulated emission of a single whispering gallery mode up to ∼2 MW/cm2 and multimode lasing with a threshold of 2.86 MW/cm2 from an as-grown microrod under optical excitation at room temperature.
Keywords: GaN; growth; lasing; microrods; MOVPE; whispering gallery modes